Patient-Provider Communication Training for Dysarthria: Lessons Learned from Student Trainees - Burns, Michael; Baylor, Carolyn; Yorkston, Kathryn (Seminars in Speech and Language, 2017)
Patient-provider communication skills training programs rarely include content addressing how health care providers can improve communication with patients exhibiting dysarthria and other communication disorders. Consequently, these patients often struggle to access quality health care services. This article describes a training program focused on giving health care students the opportunity to interact with standardized patients portraying dysarthria and aphasia. A summary of the program's outcome is then provided from the perspective of the students involved as well as lessons students taught us about how to continue improving this type of program and to make it a more universal part of health care education.
Keywords: Patient-provider communication; dysarthria; medical education